ANALISIS KARAKTERISTIK SOSIAL EKONOMI YANG MEMANFAATKAN JASA PEGADAIAN DI KOTA MEDAN - Julita SE,M.Si; Mawardi Nur, SE (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2008)
In the preamble 1945 states that the aim of a state is to achieve the righteous and prosperous people. In order to support the  great and independent national economy, the economic depelopment needs to get in appropriate order to increase the people’s income and to overcome inbalanced economy and social gap. The government gives some service, protection and welfare as its responsibility, so each people can fulfill their needs to gain the welfare for those people who live in Indonesia.            This research made to know the characteristic of  social economic people that use the government services such as pawnshop in Medan. It made also to know whether there is a relationship or not between social economic characteristic and service (the amount of money owed) in the pawnshop and to find out the most dominant social economic characteristic in using the pawnshop in Medan.            The number of sample in this research is 170 which consist of 17 pawnshop branch offices in Medan. Each office was given a questionnaire for 10 person who used the pawnshop’s service. The tenth person were taken randomly. In findings, the characteristics of  social economy that is represented by the income’s factors, the number of families and educations affects the amount of money owed and the most dominat factor  of it is the consumer’s income  and the numbers of families . The cause is the consumer’s income that regarded as one of the terms which should be asked in having a loan, while the number of  families is regarded as another cause of  the amount of the money owed. The bigger of the number of families influenced the bigger needs, so that the pawnshop is chosen as the one of alternative ways to fulfil the needs. The most dominant effect given by the social economic characteristic to the amount of money owed is 55,7% and the rest is 44,3 % it is influenced by another factors, such as the guarantee, the limit of time, the interest rate and administration given to the consumers.